How the COVID-19 pandemic changed stakeholder engagement processes in sustainability research in the long-term [version 1; peer review: 1 approved, 2 approved with reservations] - Johan Lilliestam; Andrzej Ceglarz; Amanda Schibline; Diana Süsser; Pia-Johanna Schweizer; Vassilis Stavrakas (F1000Research, 2024)
Background The COVID-19 pandemic affected stakeholder engagement in sustainability research projects in many ways. But which effects appear permanent today, after the pandemic ended? Methods To address this, we interviewed researchers and stakeholders and carried out a survey among European sustainability research projects in 2022. Results We find that the pandemic years disrupted stakeholder-based research, also with lasting effects. The forced shift to online modes showed how digital engagement can bring benefits in terms of easier and more efficient stakeholder engagement, but also that important aspects are lost, particularly regarding intensity of collaboration and depth of insights. Whether to go online or stay offline depends largely on the research objective, which stakeholders to involve, and how well researchers and stakeholders already know each other. Most researchers and stakeholders want to continue online collaboration in the long term, especially those with positive online collaboration experiences from the pandemic years. Conclusions The pandemic has a long-term impact on stakeholder engagement in research; online engagement cannot replace all benefit of previous in-person interactions with stakeholders, but it has led to digital innovations and expanded the engagement portfolio. Our research has provided qualitative insights into the impact of the pandemic on stakeholder engagement in various sustainability research projects and the implications for the long-term future that are relevant to researchers and funding agencies.